The Role of Digital Technology in Improving Nutrition Education for Millennials and Generation Z - Andi nursiah (Pt. Anagata Sembagi Education, 2024)
Digital technology has brought about a revolution in personalized nutrition for Millennials and Z generations, who increasingly rely on artificial intelligence (AI)-based apps for dietary recommendations tailored to individual needs. These apps analyze personal data such as weight, height, physical activity and food preferences to provide more relevant advice. Devices such as smartwatches also help track diet and healthy living habits. However, challenges related to data privacy and security are still major issues that require strict regulation. On the other hand, digital technology is also expanding access to nutrition education through more interactive e-learning platforms, webinars and digital modules, enabling more enjoyable and effective learning. In addition, online communities that support healthy lifestyles are growing in popularity, providing motivation and useful information. Gamification approaches in nutrition education also help encourage active participation with diet challenges and virtual rewards. However, the digital divide in remote areas remains a major obstacle in ensuring equitable access. This research aims to explore the role of digital technology in improving nutrition awareness among the younger generation, using a qualitative approach through phenomenological and case study studies. The findings are expected to provide insights into the potential and challenges of using technology in nutrition education as well as recommendations for more inclusive and safe development